An e-Commerce system for sales and purchase order management of machinery hardware / Tan Lian Kee - Tan, Lian Kee (2002)
This report documents the explanations and descriptions of doing online business, which is defined as e-Commerce system, requirement and designs of the project. Therefore, this documentation is including four chapters which also describing the introduction, literature review, system analysis, methodology and design of the system. This report is int reducing the project scopes initially. It describes the actual meaning of the online sales and purchases order, the purposes of using the online technique to do business. objectives, and outcomes of the project. The Literature Review summarized the findings and reports the background of the project topic. System Analysis and Methodology chapter gives a detail description to the analysis requirements; approach to be adapted and other general statements. In the Chapter of System Design, Data Flow diagrams and flowcharts are drawn to present the flows of the system modules and the whole system. Moreover, this report will show the System Implementation, system Testing and System Evaluation part. The System Implementation describes the stage to change the thing from the scratch to the reality. The flowchart design for each module and the file structure design for each table in the database as well as the interface design arc move from the design scratch to the real implementation stage have using hardware development requirement and software development tools. The System Testing describes the process of executing a program with the intention of finding bugs, errors or defects that present in the system. System testing also can be defined us the process of analyzing a software item to detect the difference between existing and required conditions and to evaluate the features of the software items. Also, the System Evaluation can be described as conclusion, which will show various problems were encountered. These entire problems were solved through research and studies Every system also has it own strengths, limitations and future enhancements where can be identified.